The data analysis workshop : solve business problems with state-of-the-art data analysis models, developing expert data analysis skills along the way /: solve business problems with state-of-the-art data analysis models, developing expert data analysis skills along the way. (2020) - Govindan, Gururajan; Hora, Shubhangi; Palagachev, Konstantin
No abstract available